Yusoh wood store inventory system /Siti Aisyah Yusoh - Yusoh, Siti Aisyah (2012)
Yusoh wood Store is a company that provides all kinds of woods. Currently, the company is using manual system in storing data and inventory process. Sometimes, staffs in the company faced with some problems such as stock out, get the wrong inventory information and also lost some stock out and stock in details. The inventory system is a system or software that can help manage the inventory process in the company. All the product transaction has been stored in the system. After the customer buys the product, the staffs will fill the stock out and stock in form to store all the transactions. Each product will have their maximum level, minimum level and reorder level. The system is developed to enhance the storing process of inventory transaction and also store all the information about product info. The system is simple and easy to manage. This system has been developed based on Waterfall model that consists of Analysis, design, implementation, testing and integration and operation & maintenance. After the development has been done, user testing was distributed to get some feedback from user. Based on the evaluations that have been done, the system meets the user requirement and achieved the objectives of the system. The feedback from the staff is good and positive. The result shows that the system is usable and can help staff manage the inventory process. The inventory system has given a positive impact to the company performance.